Carotid surgery - Danza, Rómulo; de Sobregrau, Rafael; Fuster, Bartolomé; Grillo, Bartolomé; Mazza, Milton; Palma, Eduardo; Torres, Carlos; Ugarte, Raúl (Cirugía del Uruguay, 1980)
Analysis of diseases of extracranial carotid artery which can be treated by surgery, in particular arterioscl'erosis and its connection with cerebro vascular insufficiency. The members evaluated the different invasive and non - invasive methods of establishing diagnosis and set forth guidelines fo